2016
DOI: 10.1111/gcbb.12395
|View full text |Cite
|
Sign up to set email alerts
|

Landscape control of nitrous oxide emissions during the transition from conservation reserve program to perennial grasses for bioenergy

Abstract: Future liquid fuel demand from renewable sources may, in part, be met by converting the seasonally wet portions of the landscape currently managed for soil and water conservation to perennial energy crops. However, this shift may increase nitrous oxide (N 2 O) emissions, thus limiting the carbon (C) benefits of energy crops. Particularly high emissions may occur during the transition period when the soil is disturbed, plants are establishing, and nitrate and water accumulation may favor emissions. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 44 publications
(58 reference statements)
1
34
0
Order By: Relevance
“…Similar N 2 O emissions events have been previously reported after rainfall (e.g. Breuer, Papen, & Butterbach‐Bahl, ; Mummey, Smith, & Bolton, ; Saha et al, ), and we suggest that the driver of the event reported in this paper was that nitrate (NO 3 ) built up in the soil during the preceding dry weeks, which was rapidly denitrified as the soil became anaerobic following the rainfall, a process experimentally described elsewhere (Krichels, DeLucia, Sanford, Chee‐Sanford, & Yang, ). This event reinforces the necessity to measure GHG fluxes at a temporal resolution appropriate to detect such emission events.…”
Section: Discussionsupporting
confidence: 90%
“…Similar N 2 O emissions events have been previously reported after rainfall (e.g. Breuer, Papen, & Butterbach‐Bahl, ; Mummey, Smith, & Bolton, ; Saha et al, ), and we suggest that the driver of the event reported in this paper was that nitrate (NO 3 ) built up in the soil during the preceding dry weeks, which was rapidly denitrified as the soil became anaerobic following the rainfall, a process experimentally described elsewhere (Krichels, DeLucia, Sanford, Chee‐Sanford, & Yang, ). This event reinforces the necessity to measure GHG fluxes at a temporal resolution appropriate to detect such emission events.…”
Section: Discussionsupporting
confidence: 90%
“…At each monitoring location and soil depth, θ A was calculated from half‐hourly volumetric soil moisture measurements, soil porosity, and rock volume (see Saha et al, ). Since Saha et al () showed that a regression tree predicted higher N 2 O emissions in the same experimental site when θ A < 0.03 m 3 m −3 and when soil NO 3 availability was not limiting, we assumed θ A = 0.03 m 3 m −3 to be a threshold below which emissions unusually increase (Saha et al, ). The cumulative frequency (i.e., counts) of θ A < 0.03 m 3 m −3 was natural log transformed (for visual scaling), spatially interpolated, and overlaid with the temporal stability of growing season N 2 O flux.…”
Section: Methodsmentioning
confidence: 99%
“…Emissions of the greenhouse gas nitrous oxide (N 2 O) from soils often exhibit high spatial and temporal variability (Izaurralde et al, 2004;Pennock et al, 1992;Saha et al, 2017;van Kessel et al, 1993;Vilain et al, 2010). This variability emerges from the collective forcing by hydrologic and biogeochemical factors that control soil nitrogen (N) transformations, which are in turn spatially and temporally variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been made in quantifying growing cycle N 2 O emissions from biomass production but the start and end of crop life are still poorly quantified, despite these being the periods of greatest soil perturbation and C and N inputs (Whitaker et al, 2017). Although there have been some studies investigating GHG fluxes during conversion periods to energy crops (e.g., Nikièma, Rothstein, & Miller, 2012;Oates et al, 2015;Palmer et al, 2014;Roth et al, 2013;Saha et al, 2017) and others investigating the impacts of fertiliser additions on N 2 O emissions (Behnke et al, 2012;Drewer, Finch, Lloyd, Baggs, & Skiba, 2012;Duran, Duncan, Oates, Kucharik, & Jackson, 2016;Gauder, Butterbach-Bahl, Graeff-Honninger, Claupein, & Wiegel, 2012;Hellebrand, Scholz, Kern, & Kavdir, 2005;Jørgensen, Jorgensen, Nielsen, Maag, & Lind, 1997;Roth et al, 2015;Ruan, Bhardwaj, Hamilton, & Robertson, 2016), surprisingly, little work has considered GHG dynamics at the end of cropping cycles with reversion back to more typical agricultural systems. One study looked into the reversion of a 20-year-old Miscanthus x giganteus plantation into wheat production and set-aside (Drewer, DufossĂŠ, Skiba, & Gabrielle, 2014;DufossĂŠ, Drewer, Gabrielle, & Drouet, 2014).…”
mentioning
confidence: 99%